1997
DOI: 10.1021/bi9705725
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a DNA Duplex Containing the Exocyclic Lesion 3,N4-Etheno-2‘-deoxycytidine Opposite 2‘-Deoxyguanosine

Abstract: Vinyl chloride reacts with cellular DNA producing 3,N4-etheno-2'-deoxycytidine (epsilonC) along with other exocyclic adducts. The solution structure of an oligodeoxynucleotide duplex containing an epsilonC.dG base pair was determined by high-resolution NMR spectroscopy and molecular dynamics simulations. NMR data indicated that the duplex adopts a right-handed helical structure having all residues in anti orientation around the glycosylic torsion angle. The epsilonC adduct has a sugar pucker in the C3'-endo/C4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…In addition, the base pairing preferences are similar for both the 8-HM-εC and εC-containing oligonucleotides. The latter compound is closely related structurally to 8-HM-εC and it has been established that it is a mutagenic lesion (24)(25)(26)(27)(28)(29). Moreover, by molecular modeling, we showed that little difference exists in the planarity and sugar conformations of the two derivatives in duplex DNA.…”
Section: Introductionmentioning
confidence: 67%
“…In addition, the base pairing preferences are similar for both the 8-HM-εC and εC-containing oligonucleotides. The latter compound is closely related structurally to 8-HM-εC and it has been established that it is a mutagenic lesion (24)(25)(26)(27)(28)(29). Moreover, by molecular modeling, we showed that little difference exists in the planarity and sugar conformations of the two derivatives in duplex DNA.…”
Section: Introductionmentioning
confidence: 67%
“…Also, the guanine and thymine are stacked well with the adjacent bases in the DNA helix. Although the NMR structure of a G ⅐ ⑀ C base pair reveals a similar wobble geometry, this base pair is much more distorted, and there is only one hydrogen bond between the ethenocytosine and the guanine (42). In addition to this weaker hydrogen bonding, the ethenocytosine base is very poorly stacked with the adjacent bases, suggesting that the G ⅐ ⑀ C base pair is considerably less stable than a G ⅐T mismatch.…”
Section: Discussionmentioning
confidence: 98%
“…Schematic diagram of the normal Watson-Crick A⅐T base pair and the two mismatches, G ⅐T and G ⅐ ⑀ C. The G ⅐T mismatch is based on the structures found by NMR (41) and crystallographic (40) studies. The G ⅐ ⑀ C base pair is based on a structure determined by NMR (42). Note that in the A⅐T and G ⅐T structures the two bases of each base pair are in the same plane, whereas in the G ⅐ ⑀ C structure the ethenocytosine is distorted out of the plane preventing proper stacking with the flanking bases.…”
Section: Discussionmentioning
confidence: 99%
“…Specific binding of ANPG to ⑀C⅐G suggests that the enzyme recognizes ⑀C in the active site pocket; however, in contrast to MUG and hTDG, is not able to excise the adduct. Cullinan et al (53,54) have shown by computer modeling that the ⑀C nucleoside fits neatly into the active site of ANPG. However, these authors proposed that ANPG is not able to extrude the ⑀C residue from duplex DNA.…”
Section: Discussionmentioning
confidence: 99%